2014
DOI: 10.3389/fimmu.2014.00507
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Obesity in Treated Female HIV Patients from Sub-Saharan Africa: Potential Causes and Possible Targets for Intervention

Abstract: Objectives: To investigate changing nutritional demographics of treated HIV-1-infected patients and explore causes of obesity, particularly in women of African origin.Methods: We prospectively reviewed nutritional demographics of clinic attenders at an urban European HIV clinic during four one-month periods at three-yearly intervals (2001, 2004, 2007, and 2010) and in two consecutive whole-year reviews (2010–2011 and 2011–2012). Risk-factors for obesity were assessed by multiple linear regression. A sub-study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
21
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 45 publications
7
21
1
Order By: Relevance
“…The prevalence of abdominal obesity in our study is comparable to the 30% observed in a Southwestern Ugandan ART cohort [26] but was lower than that reported in the background GPC population-56% [10]. High prevalence of obesity among women than men has also been previously established by studies in SSA (24-26) and Europe [29]. The observed risk of obesity from PI-based ART corroborates results from a US based observational study [30] and is possibly attributed to ART associated metabolic aberrations and fat mal-distribution.…”
Section: Discussionsupporting
confidence: 83%
“…The prevalence of abdominal obesity in our study is comparable to the 30% observed in a Southwestern Ugandan ART cohort [26] but was lower than that reported in the background GPC population-56% [10]. High prevalence of obesity among women than men has also been previously established by studies in SSA (24-26) and Europe [29]. The observed risk of obesity from PI-based ART corroborates results from a US based observational study [30] and is possibly attributed to ART associated metabolic aberrations and fat mal-distribution.…”
Section: Discussionsupporting
confidence: 83%
“…Although weight loss and underweight are independently associated with increased risk of disability and death, 18 this study suggests that many patients, especially females, who are clinically stable and on lifelong HAART, are at greater risk of overweight and obesity than severe malnutrition. This is consistent with other studies that found obesity to be more prevalent than wasting in patients on lifelong HAART 16,19,20 and non-white females to be at greater risk. 19,20 Previous South African studies 15,16 have reported weight gain following the initiation of ART, particularly in African females, and possible reasons proposed for this include the stigma of weight loss, thinness being associated with HIV and/or TB infection and poor health, cultural norms regarding what is considered to be ideal body size, and the belief that 'bigger is better' .…”
Section: Assessment Of Phc Facilitysupporting
confidence: 82%
“…This is consistent with other studies that found obesity to be more prevalent than wasting in patients on lifelong HAART 16,19,20 and non-white females to be at greater risk. 19,20 Previous South African studies 15,16 have reported weight gain following the initiation of ART, particularly in African females, and possible reasons proposed for this include the stigma of weight loss, thinness being associated with HIV and/or TB infection and poor health, cultural norms regarding what is considered to be ideal body size, and the belief that 'bigger is better' . 15,21 This perception is also consistent with other studies, 15 where the desire has been reported for HIV-positive individuals to achieve and maintain what is considered to be a 'healthy' overweight body size.…”
Section: Assessment Of Phc Facilitysupporting
confidence: 82%
“…Although most women chose figures that were within one BMI category of their actual figures (e.g., overweight women indicated normal weight figures), these slightly inaccurate self‐perceptions could have important health implications because overweight status is associated with increased risk for noncommunicable diseases (World Health Organization, ). Similar research studies across sub‐Saharan Africa have found that women tend to perceive their figures as smaller than their actual body sizes (Devanathan et al, ; Matoti‐Mvalo & Puoane, ; McCormick et al, ; Muhihi et al, ; Njecko, Meyer, Ashu, & Gobte, ; Puoane et al, ). Although our results matched these findings for overweight women, who tended to underestimate their current sizes, we conversely found that underweight women tended to overestimate their current sizes.…”
Section: Discussionmentioning
confidence: 66%